2016
DOI: 10.1115/1.4032436
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Modeling of Brain Tissue: Current Perspectives

Abstract: Modeling the mechanical response of the brain has become increasingly important over the past decades. Although mechanical stimuli to the brain are small under physiological conditions, mechanics plays a significant role under pathological conditions including brain development, brain injury, and brain surgery. Well calibrated and validated constitutive models for brain tissue are essential to accurately simulate these phenomena. A variety of constitutive models have been proposed over the past three decades, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 87 publications
(215 reference statements)
1
86
0
Order By: Relevance
“…Most constitutive models of the brain require assumptions about viscosity [36], and it has been recently demonstrated that both viscous and elastic properties of hydrogels can regulate cell behavior [54]. …”
Section: Resultsmentioning
confidence: 99%
“…Most constitutive models of the brain require assumptions about viscosity [36], and it has been recently demonstrated that both viscous and elastic properties of hydrogels can regulate cell behavior [54]. …”
Section: Resultsmentioning
confidence: 99%
“…By contrast, MRE shows fluidization with age (and that female brains are more elastic than male brains) 65 . Such discrepancies are not uncommon in this field and are widely discussed 22,47,51,65,66 . They could emanate from different preparative procedures of the tissue, time and length scales, as well as modes of deformation, and the change of properties between in vivo and in vitro measurements, among other possible factors.…”
Section: Tissue Considerationsmentioning
confidence: 97%
“…They could emanate from different preparative procedures of the tissue, time and length scales, as well as modes of deformation, and the change of properties between in vivo and in vitro measurements, among other possible factors. Improved microscopic models of brain tissue might help to resolve these differences in the future 49,66 .…”
Section: Tissue Considerationsmentioning
confidence: 99%
“…Specifically, the mesh has all size features comparable to or smaller than neuron soma and bending stiffness values of ∌0.1 nN·m, comparable to a 150-ÎŒm-thick brain tissue slice (i.e., the same as the overall implanted open mesh diameter), ∌0.4 nN·m (27,28) and orders of magnitude smaller (more flexible) than conventional probes (14,29,30). Herein, we present systematic time-dependent histology studies of the mesh electronics/brain-tissue interface obtained from tissue sections perpendicular (horizontal slices) and parallel (sagittal slices) to the long axis of probes, as well as time-dependent measurements obtained from horizontal tissue sections containing the cross-sections Significance Seamless integration of electrical probes within neural tissue could substantially enhance their impact and open up new opportunities in neuroscience research through electronic therapeutics.…”
mentioning
confidence: 99%